A review of the origin of equiaxed grains during solidification under mechanical stirring, vibration, electromagnetic, electric-current, and ultrasonic treatments. (1st May 2023) - Balasubramani, Nagasivamuni; Venezuela, Jeffrey; StJohn, David; Wang, Gui; Dargusch, Matthew
Highlights: The origin of fine grains was reviewed for prominent melt processing methods. Different solidification conditions are reviewed for the origin of fine grains. Agitation can induce separation of fine grains from cold zones of a casting. Mould wall, melt surface and vibrating surfaces are the coldest zones. Separation mechanism is the dominant mode for the formation of fine grains. Abstract: Refinement of grains and intermetallic phases in the as-solidified alloy structure offers uniform structural properties, eliminates or minimizes common solidification defects, including segregation and hot cracking, and improves thermomechanical processing of wrought alloys. Melt processing by an external field is an efficient process for achieving refinement of the solidification structure of Al and Mg alloys without altering the alloy composition. A wide range of melt processing methods and solidification studies (conventional, directional, and in-situ approaches) have been reported in the literature that explore the mechanism of refinement. Identifying the dominant grain refinement mechanism has been a focus of most investigations because significant variations exist according to the casting conditions and the type of applied external treatments. The origin of fine grains occurs through either one or a combination of heterogenous nucleation, fragmentation of dendrites and grains formed and then separated from the surface of the melt and mould wall under vibration or agitation. The first part of this review describes the prominent external field techniques and the mechanisms proposed for the origin of fine grains. The second part critically compares the current understanding of these grain refinement mechanisms to determine differences and commonalities to identify the factors that promote the formation of equiaxed zones occupying a large volume fraction of the casting. Graphical abstract: Image, graphical abstract